Comparison of Peripheral Blood Regulatory T Cells and Functional Subsets Between Ocular and Generalized Myasthenia Gravis - Rao, Jie; Li, Siyu; Wang, Xinyu; Cheng, Qi; Ji, Yu; Fu, Wenwen; Huang, Hui; Shi, Ling; Wu, Xiaorong (Frontiers in Medicine, 2022)
Purpose: This study aims to discuss the function mechanism of regulatory T cells and its subsets in the pathogenic process of myasthenia gravies by contracting the activation levels of those cells in peripheral blood among healthy people, ocular myasthenia gravies patients and generalized myasthenia gravies patients. Method: Healthy people, newly diagnosed oMG patients and gMG patients were enrolled in this study. The percentage of the CD3+CD4+ T cells, CD3+CD4+CD25+ Treg cells, CD3+CD4+CD25+Foxp3+ Treg cells, CD3+CD4+CD25+Foxp3hi CD45RA- aTreg, CD3+CD4+CD25+Foxp3loCD45RA- n-sTreg cells and CD3+CD4+CD25+ Foxp3loCD45RA+ rTreg cells in the peripheral blood were examined by flow cytometry. And then analyzed the differences of Treg cells and its subsets among the study members. Results: There was some difference among oMG patients，gMG patients and HCs in the percentage of the CD3+CD4+ T cells, CD3+CD4+CD25+ Treg cells, CD3+CD4+CD25+Foxp3+ Treg cells, CD3+CD4+CD25+Foxp3hi CD45RA- aTreg, CD3+CD4+CD25+Foxp3loCD45RA- n-sTreg cells and CD3+CD4+CD25+ Foxp3loCD45RA+ rTreg cells Conclusion: The changes in the number and function of Treg cells and its subsets can cause the impairment of negative immune regulation, which may mediate the triggering of oMG and its progression to gMG.